PENGARUH BRAND AMBASSADOR BLACKPINK TERHADAP CITRA PERUSAHAAN SHOPEE PADA MAHASISWI DI UIN SUSKA RIAU - Raswen, Rima Nabila; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Shopee application relies on content and services in e-commerce that are used and many carry out promotions in the form of advertisements and use of brand ambassadors. This brand ambassador is intended to provide a stimulus for consumers to attract consumers so that consumers have a positive opinion of company shopee's image. The theory used in this study is S-R. The purpose of this study was to find out how much influence the BLACKPINK  Brand Ambassador had on Company Citra Shopee on female students at Uin Suska Riau.The quantitative approach was applyed in this research to 100 female student respondents who use Shopee application with a judgemental  sampling technique and then formula slovin. This reseacrh used questionnaire for collecting data in Brand Ambassador (X) and Brand Image(Y). questionnaires and documentation were distributed in 8 facultiesat UIN Suska Riau. While Data analysis techniques use descriptive and inferential statistics to prove the hypothesis.The results of this study indicate that the value of tcount (4.476)> t table (1.98) with the significance value of 0,000 is still below 0.05, then the hypothesis in this study is accepted. This explains that there is the influence of the BLACKPINK Brand Ambassador (variable X) on the Shopee Image (variable Y) at the Student at UIN Suska Riau. Meanwhile, the influence of the BLACKPINK Brand Ambassador (variable X) on the Shopee Image (variable Y) on female students at UIN Suska Riau is 17.0%. While the remaining 83.0% is influenced by other variables not included in this study. Based on the result , this research suggested the company to use BLACKPINK as Brand Ambassador for improving shopee image. In from to improve trusted and product sale.